A systematic review on bio-sequestration of carbon dioxide in bio-concrete systems: a future direction - Alshalif, Abdullah Faisal; M. Irwan, J.; Othman, N.; Al-Gheethi, A. A.; Shamsudin, S. (Taylor & Francis, 2022)
The paper reviewed the current perspectives on the development of carbon dioxide (CO2) sequestration through its process conversion into calcite. The process occurs in either geological or biological systems. However, geological sequestration is an expensive process, which is slow in comparison to bio-sequestration. Recently, the bio-sequestration of atmospheric CO2 into the soil using microorganisms such as algae has been investigated. However, the algae cannot be used in the bio-concrete due to their nature as phototrophic organisms. In contrast, bacteria are the most potent organisms in bio-concrete technology. The use of bacterial species in the bio-aerated concrete bricks (B-ACB) and its potential to biosequestrate CO2 represents a future strategy to reduce high CO2 pollution. Bacterial cells can capture CO2 by accelerating the carbonation processes, which convert CO2 into calcium carbonate (CaCO3) via carbon anhydrase and urease enzymes. The present paper aimed to highlight and discuss the applicability of bacteria in the B-ACB for capturing and storing CO2. It is evident from the literature that the new trends to use bio-concrete might contribute to the reduction of CO2 by accelerating the carbonation process and strengthening the B-ACB.